Inauspicious Contribution of Hepatitis C Virus and Diabetes Mellitus Targeting Kidneys: An Update (Iranian Journal of Kidney Diseases, 2012)
Hepatitis C virus (HCV) infection and diabetes mellitus are frequent problems worldwide that induce high health and financial burden in different societies, both of which are also highly prevalent in patients with chronic kidney disease. Diabetes mellitus is a known underlying cause of end-stage renal disease, and on the other hand, HCV is responsible for a wide variety of renal manifestations, such as membranous nephropathy, cryoglobulinemia, and membranoproliferative glomerulonephritis. Moreover, along with its direct impact on kidney damage, HCV is also known to play a role in progression of other causes of kidney diseases. It is known that HCV infection is highly prevalent among patients with diabetic nephropathy. This article reviews the existing literature on the relationship between HCV infection and diabetes mellitus in patients with chronic kidney disease, and also overviews the interplay of these two factors in the transplantation era.